Phytocoenotic originality of the N-Adriatic coastal sand dunes (Northern Italy) in the European context: The Stipa veneta -rich communities - G. Sburlino; G. Buffa; L. Filesi; U. Gamper (Plant Biosystems, 2008)

Invited paper - C. Blasi; A. Acosta; L. Filesi; P. di Marzio (Plant Biosystems, 1999)

Relation between climate and vegetation along a Mediterranean‐Temperate boundary in central Italy - C. Blasi; M. L. Carranza; L. Filesi; A. Tilia; A. Acosta (Global Ecology and Biogeography, 1999)
Summary The relationship between climate and vegetation was investigated along a Mediterranean‐Temperate boundary in central Italy. The study area is a transition zone between the Temperate (Eurosiberian) and Mediterranean regions and has an altitudinal range of almost 1750 m. Ordination and cluster analysis were used. The results did not show any sharp boundary but a climate‐vegetation mosaic ranging from upper mountain thermotype and lower hyperhumid ombrotype with Fagus sylvatica L. woodlands at higher altitudes, to meso‐Mediterranean thermotype and lower subhumid ombrotype with Mediterranean maquis and Quercus ilex L. woods on the coast. Six phytoclimatic groups are distinguished and described in terms of climatic parameters, vegetation types and morphological and chorological traits. These parameters indicate a change without sharp discontinuities between groups. The Mediterranean to Temperate transition in this Tyrrhenian sector is broad and includes most of the study area.